Analise citotoxica de esparfloxacino e seus produtos de degradaçao em células mononucleares humanas - Marona, Hérida Regina Nunes; Schapoval, Elfrides Eva Scherman; Nardi, Nance Beyer [UNESP] (My University, 2002)
Sparfloxacin, a difluorquinolone derivative, is a potent antibacterial agent active against a wide range of gram-positive and gram-negative organisms including Streptococcus pneumoniae, Staphylococcus aureus, methicillin resistant S. aureus, Legionella spp, Mycoplasma spp; Chlamydia spp. and Mycobacteria. A drawback of fluorquinolones is their photoreactivity. Sparfloxacin has been studied in terms of therapeutic activities. However, few reports about analytical methods of sparfloxacin are available in the literature. The aim of this study was to determine cytotoxic effects, using sparfloxacin reference substance (SPAX-SR), sparfloxacin tablets (SPAX-COMP) and sparfloxacin tablets submitted UV light during 36 hours (SPAX-COMP.36) solution, and two isolated products (7 and 9) of SPAX-SR submitted UV-C light, in concentrations of 31.25, 62.5, 125 and 250 μg/mL by in vitro mononuclear humane culture cells. The results, statistically analyzed by Teste de Tukey, showed SPAX, SPAX-COMP and SPAX-COMP.36 solutions could reduce the cells number in these conditions. These results could not be observed for products 7 or 9. These results can suggest that isolated product can be less cytotoxic than SPAX-SR, is method can also be used to identified products degradation of sparfloxacin in stability study. However, the low activity achieved with sparfloxacin submitted to UV-light is a source of concern and requires further investigation about its photodegradation mechanism.
Cytotoxic activity of sparfloxacin and its degradation products in mononuclear human blood cells
Keywords: Antibacterial substances; Cytotoxic activity; Quinolones; Sparfloxacin fluorquinolones; quinoline derived antiinfective agent; sparfloxacin; cell culture; Chlamydia; cytotoxicity; drug degradation; drug stability; Gram negative bacterium; Gram positive bacterium; Legionella; methicillin resistant Staphylococcus aureus; mononuclear cell; Mycobacterium; Mycoplasma; photodegradation; photoreactivity; Staphylococcus aureus; statistical analysis; Streptococcus pneumoniae; tablet; ultraviolet C radiation; ultraviolet irradiation